1972
DOI: 10.1159/000259414
|View full text |Cite
|
Sign up to set email alerts
|

Syllabic Rate and Utterance Length in French

Abstract: This third article in a series presenting the results of a computer-assisted analysis of a vast data file, based on recordings of upper middle-class Parisian conversations, deals with syllabic rate and utterance length. Performance standards are established for teaching, linguistic theory and voice-processing technology. Variations in these aspects of speech are studied as functions of a number of demographic, psychological, intellectual and phonetic background parameters. Syllabic rate is found to vary as a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
2
3

Year Published

1987
1987
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(57 citation statements)
references
References 3 publications
4
48
2
3
Order By: Relevance
“…When the authors speeded up the presentation of French test words from 2.2 to 5.6 syllables per second on the average, through either faster human delivery or computerized compression, UP effects disappeared. Interestingly, the fast rate corresponded to the average normal rate of continuous speech (Malecot, Johnston, & Kiziar, 1972). Therefore, Radeau et al (1994) suggested that UP phenomena traditionally reported in the literature could arise from the abnormally slow speech rate used in the artificial laboratory situation.…”
Section: Modell the Sequential Nature Of Speech Processingmentioning
confidence: 94%
“…When the authors speeded up the presentation of French test words from 2.2 to 5.6 syllables per second on the average, through either faster human delivery or computerized compression, UP effects disappeared. Interestingly, the fast rate corresponded to the average normal rate of continuous speech (Malecot, Johnston, & Kiziar, 1972). Therefore, Radeau et al (1994) suggested that UP phenomena traditionally reported in the literature could arise from the abnormally slow speech rate used in the artificial laboratory situation.…”
Section: Modell the Sequential Nature Of Speech Processingmentioning
confidence: 94%
“…Laver (1994:158) quotes 5.3 syllables/second as a "medium articulation rate". Duez (1982) found a mean Articulation Rate of 5.2 syllables/second for a group of prominent French politicians in 'casual interviews ' and Malecot et al (1972) found a Speaking Rate of 5.95 syllables/second for a group of Parisian French speakers. These are quite similar to the results for the English speakers in the present study, although as Laver (1994) points out, a measure of syllables per unit time is not a good basis for comparison of rate across languages because of possible differences in syllable structure.…”
Section: Discussionmentioning
confidence: 98%
“…Walker (1988) found no evidence of a difference according to gender in her study. Malecot et al (1972) found no evidence that emotional state influences speech rate.…”
Section: Measurements Of Speech Ratementioning
confidence: 93%
See 1 more Smart Citation
“…Grosjean & Deschamps (1972). Certains auteurs (dont Goldman-Eisler (1968) pour l'anglais, Malécot et al (1972) et Grosjean & Deschamps (1975) pour le français) ont soutenu que c'est la vitesse de locution qui est variable alors que la vitesse d'articulation a plutôt tendance à se maintenir. Or Miller et al (1984) ont dé-montré que la vitesse d'articulation pouvait également être variable.…”
Section: Le Débit Et La Valeur De Reproductionunclassified